Collecting Facts and Burden of Proof in Administrative Procedure - Milkov, Dragan; Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Gathering facts and means of proof in administrative procedure provides the factual basis necessary for making an administrative decision. The process of collecting facts and means of proof in administrative procedure is determined by the principle of investigation, but not in an absolute manner, without any exceptions. This is the context in which the burden of proof in administrative procedure is examined, having in mind its two basic aspects. Following the principle of investigation, the burden of proof, as a burden of production of proof, is traditionally denied in administrative procedure. An effort is made to show that this strict view is not entirely acceptable and that it has to be questioned by considering the role of the party in the process of determining the facts. On the other hand, the burden of proof can be seen as a risk of factual deficit (of non liquet situation), which is, also traditionally, divided between the administrative authority and the party, depending on whether an unfavorable or a favorable decision for the party should be made. As a general principle of division, it seems acceptable, but only conditionally, as typical, but not comprehensive, because it is not suitable for all administrative procedures.
Keywords: administrative procedure, principle of investigation in administrative procedure, proving in administrative procedure, burden of proof in administrative procedure.